Mali : Poverty Reduction Strategy Paper Annual Progress Report. (IMF Staff Country Reports; Country Report ;, 2004)
This paper reviews Mali's Poverty Reduction Strategy Paper (PRSP) Annual Progress Report. At the level of public finances and indebtedness, in recognition of the significant progress made by the government in implementing reforms, Mali has become the 7th country to reach the completion point under the reinforced Initiative for very indebted poor countries after Bolivia, Burkina Faso, Mauritania, Mozambique, Tanzania, and Uganda. The restructuring and public enterprise privatization program, involving the cotton, transportation, and telecommunications sectors is now well advanced.